Багатогранність творчої діяльності Галини Менкуш. До 60-річчя від дня народження бандуристки - Фільц, Б. (Народна творчість та етнографія, 2006)
The biographical essay contains information about different stages of life and work of bandura player Galyna Menkush: the childhood, her establishing as the musician. A detailed chronology of her creative activities during 60s — 90s is presented. A wide spectrum of Galyna Menkush's talent is offered for readers' attention: singing, acting, writing music for bandura, interpretation of folk songs, teaching, etc. The repertoire of the bandura player is analyzed.